Short-Term Effects of COVID-19-Related Deferral of Intravitreal Injection Visits - Ashkenazy N (Dove Medical Press, 2021)
Noy Ashkenazy, Lediana Goduni, William E Smiddy Department of Ophthalmology, Bascom Palmer Eye Institute, University of Miami Miller School of Medicine, Miami, FL, USACorrespondence: William E Smiddy Tel +1 305-326-6172Email wsmiddy@med.miami.eduPurpose: To determine secondary effects of the mandated COVID-19 pandemic closure period for elective treatment on non-elective, injection-based retina care and outcomes.Patients and Methods: In this cross-sectional, retrospective analysis of a single-provider outpatient clinic across multiple satellites, consecutive patients returning for intravitreal injections (IVIs) of anti-vascular endothelial growth factor or corticosteroids were identified as “delayed” or “undelayed” during a six-week study interval during the COVID-19 pandemic that closely following a mandated period of prohibited elective encounters. A “delayed” encounter was defined as having a follow-up interval exceeding 33% of the recommended cycle. Patients seen for IVIs during the corresponding six-week interval a year previously were identified for study as pre-COVID-19 controls. Main outcome measures included best-corrected visual acuity (BCVA) and optical coherence tomography (OCT) assessment based on findings of intraretinal or subretinal fluid consistent with new or recurrent neovascular events.Results: The study included 183 eyes of 144 patients who underwent IVI-based care from June 18, 2020, through August 7, 2020, compared to 193 eyes of 154 patients injected during the corresponding interval 1 year before. There were 62 eyes of 46 patients seen in the study period later than scheduled (among 144 patients of 183 eyes in total), which represented a larger proportion of delayed patients compared to the previous year (31.9% vs. 14.9%, p< 0.0005). Considering the patterns from the control group, the attributed delay due to COVID-19 was 15.0% of patients. The delayed return eyes had a greater decline in BCVA (3 letters), higher rates of worsened OCT results (48%), and prompted reduction in previously prescribed injection intervals (p< 0.02).Conclusion: The unintended consequence of delayed care of patients on established care regimens should be anticipated, and mitigate strategies considered if similar restrictions are mandated in the future.Keywords: COVID-19, SARS-CoV-2, pandemic, retinal vascular diseases, anti-vascular endothelial growth factor, treatment outcomes